The Challenge of Developing a Regional Palliative Care Data System: A Tale of Two Cities - Critchley, Patrick P.; Lohfeld, Lynne; Maxwell, David; Mcintyre, Paul; Reyno, Leonard (Journal of palliative care, 2002)
This article reviews the purposes of health care databases and the findings from a literature review of the use of patient databases in palliative care. We present the history and goals of databases developed in two Canadian settings, Hamilton and Halifax. We present data on the strengths, limitations, and difficulties encountered in each setting. We review the types of data collected and the potential of these databases, and we offer practical recommendations for others looking to set up such systems.